Peran Bhabinkamtibmas Polres Tapanuli Tengah Guna Menekan Terjadinya Tindak Pidana dalam Rangka Terpeliharanya Kamtibmas di Kabupaten Tapanuli Tengah - Zulmansyah Tanjung; Isnaini Isnaini; M. Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study is to examine the role, position, actualization of the role and barriers to the Bhabinkamtibmas of the Central Tapanuli Resort Police in order to suppress the occurrence of criminal acts in the context of maintaining security and order. The type of research used is empirical legal research with field data through interviews with officials at the Central Tapanuli Resort Police. This study uses a statutory approach and a case approach. Data analysis in this study was carried out by selecting secondary data from library research and primary data from field research and analyzed qualitatively. The conclusion in this study is that the role and position of Bhabinkamtibmas normatively regulated in the Regulation of the Head of the National Police of the Republic of Indonesia Number 3 of 2015 concerning Community Policing, the actualization of the role of Bhabinkamtibmas of the Central Tapanuli Police in order to suppress the occurrence of criminal acts in the framework of maintaining public security and order in the District Central Tapanuli has been carried out according to statutory provisions. Obstacles in actualizing the role of Bhabinkamtibmas of the Central Tapanuli Resort Police to suppress the occurrence of criminal acts in the context of maintaining public security and order in Central Tapanuli Regency are found in aspects of this legal structure including Bhabinkamtibmas personnel who are still lacking in the quantity and facilities needed are not adequate.